2005
DOI: 10.1007/s11273-004-6073-4
|View full text |Cite
|
Sign up to set email alerts
|

Young Mangrove Stands Produce a Large and High Quality Litter Input to Aquatic Systems

Abstract: Mangrove swamps are key ecosystems along the Vietnam coast. Although mangrove litter is thought to represent an important input of organic matter and nutrients to the coastal aquatic systems, the factors determining the quality and size of this litter flux have not been studied so far. We monitored leaf, stipule, twig, and reproductive litter monthly in monocultures of Rhizophora apiculata mangrove forests of 7, 11, 17 and 24 years old in the Camau province, Mekong Delta, Vietnam. Litter traps were used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
3
10
0
1
Order By: Relevance
“…Productivity difference within replanted forests could be due to stand ages, with older plantations producing significantly more propagules that young stand. Similar results were observed by Nga et al (), who reported higher propagule production in 17 and 24 years plantation than in 7 and 11‐year‐old stands of Rhizophora apiculata in Vietnam. These results have implications for the conservation and management of older mangrove stands as seed sources.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Productivity difference within replanted forests could be due to stand ages, with older plantations producing significantly more propagules that young stand. Similar results were observed by Nga et al (), who reported higher propagule production in 17 and 24 years plantation than in 7 and 11‐year‐old stands of Rhizophora apiculata in Vietnam. These results have implications for the conservation and management of older mangrove stands as seed sources.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors (e.g. Shunula & Whittick ; Nga et al ; Bernini & Rezende ) have observed year round leaf fall, whereas Slim et al () and Arreola‐Lizarraga et al () observed seasonal pattern in mangrove leaf fall, a factor associated with local climatic conditions. Differences in propagules production between reforested and natural mangroves could be due to a combination of age and management practices of the stands.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the effects of mangrove leaves on shrimp farming have not been well studied. Nga et al (2005) recently established a positive relation between the input of litter and shrimp production in the ditches. In a practical sense, this result means that an increase in litter input (70% of which consists of leaves) can boost shrimp production -unless the benefits of the presence of leaves are neutralized by the detrimental effects mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Following restoration of mangrove forests, ecosystem components and processes including leaf litter production, microbiological activity, and faunal communities change with environmental factors (Clough et al ; Nga et al ; Chen et al ; Ye et al ; Li & Ye ). It has been suggested that ecosystem processes require more time than ecosystem components to reach levels equivalent to those of a mature forest (Osland et al ; Ye et al ; Chen et al ).…”
Section: Discussionmentioning
confidence: 99%